Trends in socioeconomic inequalities in behavioural non-communicable disease risk factors: analysis of repeated cross-sectional health surveys in England between 2003 and 2019 - Fatai Ogunlayi; Paul C. Coleman; Linda Ng Fat; Jennifer S. Mindell; Oyinlola Oyebode (BMC, 2023)
Abstract Background Previous studies have shown that those in lower socioeconomic positions (SEPs) generally have higher levels of behavioural non-communicable disease (NCD) risk factors. However, there are limited studies examining recent trends in inequalities. This study examined trends in socioeconomic inequalities in NCD behavioural risk factors and their co-occurrence in England from 2003-19. Methods This time-trend analysis of repeated cross-sectional data from the Health Survey for England examined the relative index of inequalities (RII) and slope index of inequalities (SII) in four NCD behavioural risk factors: smoking; drinking above recommended limits; insufficient fruit and vegetables consumption; and physical inactivity. Findings Prevalence of risk factors has reduced over time, however, this has not been consistent across SEPs. Absolute and relative inequalities increased for physical inactivity; relative inequalities also increased for smoking; for insufficient fruit and vegetable consumption, the trends in inequalities depended on SEPs measure. Those in lower SEPs experienced persistent socioeconomic inequalities and clustering of behavioural risk factors. In contrast, those in higher SEPs had higher prevalence of excessive alcohol consumption; this inequality widened over the study period. Interpretation Inequalities in smoking and physical inactivity are persisting or widening. The pattern of higher drinking in higher SEPs obscure the fact that the greatest burden of alcohol-related harm falls on lower SEPs. Policy attention is required to tackle increasing inequalities in smoking prevalence, low fruit and vegetable consumption and physical inactivity, and to reduce alcohol harm.